Nitrous oxide emissions associated with land use change to bioenergy crops Miscanthus x giganteus and Phalaris arundinacea - Krol, Dominika Joanna (Trinity College (Dublin, Ireland). Department of Botany, 2013)
Bioenergy crops are an increasingly popular alternative to fossil fuels for electricity and heat generation due to their substantial yields combined with low inputs of resources. As these crops are characterised by low nutrient requirements, they can facilitate mitigation of fertiliser-induced gaseous emissions and consequently aid meeting the greenhouse gas (GHG) reduction targets posed by various policies. However very little research on GHG emissions associated with the cultivation of the energy crops is available. Nitrous oxide (N2O) emissions dominate the GHG budget of tillage and pastoral soils (Rees and Ball, 2010) therefore monitoring of N2O from these soils is crucial. This study investigated the impact of land-use change (LUC) from pasture to two energy grasses (Miscanthus x. giganteus and Phalaris arundinacea) on N2O emissions through a field trial and two lysimeter studies focused on investigating the effects of ploughing technique, fertiliser management, soil type and crop type.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.